PEMANFAATAN FOTO UDARA PANKROMATIK HITAM PUTIH DAN SISTEM INFORMASI GEOGRAFI UNTUK MENENTUKAN LOKASI KAWASAN INDUSTRI SEKUNDER DI KECAMATAN SENTOLO KABUPATEN KULON PROGO - , ARIS WIDARSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The industrial development in Indonesia as a developing country characterized by physically building construction industry. The existence of the industrial buildings bring a positive impact on the environment and society, such as creating jobs. But on the other hand, industrial buildings also have negative impacts, such as environmental pollution and abandonment of land suitability factors, as an example is wetland used for industrial estates. This study aimed to 1) determine the ability of aerial photo interpretation and GIS for site selection secondary industrial area in District Sentolo. 2) Prioritize the suitability of land for secondary industrial area in terms of the physical aspects of land based studies of remote sensing and GIS and Spatial General Plan Kulon Progo as comparative material. The method used in this study is to integrate remote sensing and Geographic Information Systems (GIS) assisted with thematic maps and equipped with field work. The parameters used in this study is a landform, land use, slope, soil texture, soil bearing capacity, depth of water table, flood susceptibility, and the distance to the main road. The method used for land suitability assessment is a tiered valuation weighted method. The results showed that aerial photographs used well enough to identify the physical parameters as proven by an average interpretation accuracy above 80%. Based on the results of data processing obtained four classes of land suitability for the location of secondary industries and three regions recommendation, which is very suitable area of 1.03 ha (0.02%), suitable area of 1243.13 ha (23.33%), less suitable area of 3534 , 49 ha (66.34%), and not suitable area of 549.11 ha (10.31%). The largest area in the class less suitable. Recommendation area I covers an area of 729.99 ha (13.70%), recommendation II covers an area of 2988.63 ha (56.10%), and the non recommend areas cover an area of 1609.14 ha (30.20%). The largest area is the recommendation area II.